Induction of Labor in Women with Oligohydramnios: Misoprostol Compared with Prostaglandin E2 - Kawakita, Tetsuya; Grantz, Katherine L.; Landy, Helain J.; Huang, Chun-Chih; Kominiarek, Michelle A. (American Journal of Perinatology, 2017)
Objective To compare perinatal outcomes in women with oligohydramnios and an unfavorable cervix undergoing labor induction with misoprostol to prostaglandin E2.Study Design We conducted a secondary analysis of women with oligohydramnios undergoing labor induction in the Consortium on Safe Labor study (2002–2008). Oligohydramnios was recorded in the medical chart. We evaluated perinatal outcomes. We limited the analysis to women with an unfavorable cervix defined by simplified Bishop score ≤ 4. Misoprostol was compared with prostaglandin E2. Women could have received oxytocin, underwent mechanical dilation, or had artificial rupture of membranes, but women who underwent induction with both misoprostol and prostaglandin E2 were excluded. We calculated adjusted odds ratios with 95% confidence intervals, controlling for maternal age, maternal body mass index (kg/m2), parity, and mechanical dilation.Results Among women with oligohydramnios and an unfavorable cervix who underwent induction of labor, 141 (39.4%) received misoprostol and 217 (60.6%) received prostaglandin E2. There were no significant differences in cesarean delivery, chorioamnionitis, postpartum hemorrhage, transfusion, neonatal intensive care unit (NICU) admission, NICU stay > 72 hours, mechanical ventilation, and neonatal sepsis.Conclusion In women with oligohydramnios and an unfavorable cervix, induction of labor with misoprostol was comparable to prostaglandin E2.
Keywords: cesarean delivery; induction; misoprostol; oligohydramnios; prostaglandin E2